2017
DOI: 10.1007/s00442-017-3904-6
|View full text |Cite
|
Sign up to set email alerts
|

The Bruce effect revisited: is pregnancy termination in female rodents an adaptation to ensure breeding success after male turnover in low densities?

Abstract: than year-born and multiparous females. Taken together, our results suggest that the Bruce effect may be an adaptive breeding strategy for rodent females in cyclic populations specifically at low densities in the increase phase, when isolated, overwintered animals associate in MF pairs. During population lows infanticide risk and inbreeding risk may then be higher than during population highs, while also the fitness value of a litter in an increasing population is higher. Therefore, the Bruce effect may be ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…24 Finally, the Bruce effect in bank voles (Myodes glareolus) occurs more frequently in circumstances that may be associated with greater infanticide risk. 78 Together, these results support the hypothesis that females may express the Bruce effect in a facultative, context-dependent manner. The details of this context-dependence need to be more fully explored within a comparative framework.…”
Section: Alternative Simulation Parameterssupporting
confidence: 68%
See 1 more Smart Citation
“…24 Finally, the Bruce effect in bank voles (Myodes glareolus) occurs more frequently in circumstances that may be associated with greater infanticide risk. 78 Together, these results support the hypothesis that females may express the Bruce effect in a facultative, context-dependent manner. The details of this context-dependence need to be more fully explored within a comparative framework.…”
Section: Alternative Simulation Parameterssupporting
confidence: 68%
“…In meadow voles, pregnancy termination following exposure to nonsire males is less likely in highly aggressive than in less aggressive females, and is more likely after exposure to highly aggressive than to less aggressive males . Finally, the Bruce effect in bank voles ( Myodes glareolus ) occurs more frequently in circumstances that may be associated with greater infanticide risk . Together, these results support the hypothesis that females may express the Bruce effect in a facultative, context‐dependent manner.…”
Section: Why Does Male‐mediated Prenatal Loss Occur?supporting
confidence: 61%
“…Gustafsson et al (1980, 1983) assumed lactational anoestrus in a laboratory colony of caged bank vole pairs, since only 2% of females ( n  = 640) conceived during lactation. Meanwhile, in semi-wild experimental bank vole populations in large outdoor enclosures, we observed that 40% of non-gravid, lactating females (Eccard and Ylönen 2003, n  = 39 females) and 9 out of 10 of non-gravid, lactating females (re-analysing data reported in Eccard et al 2017) were conceiving within days after being release to enclosures, while still accompanied by their several days-old litter.…”
Section: Introductionsupporting
confidence: 54%
“…3, Table 2) revealed a general response to the male scents independent of familiarity, which may indicate a general interest in mating and future reproduction among the females. After missing the post-partum oestrus, female bank voles seem to be able to conceive during lactation (re-analysed from Eccard and Ylönen (2003) and Eccard et al (2017), but see Gustafsson et al 1980, 1983) and interaction with male scents and males may trigger a behavioural oestrus, during which females were reported to actively visit males for mating (Klemme et al 2011). In the control treatment, we found a negative correlation between litter size and the total time spent at the scent area, as well as a negative correlation with the longest visit at the scent area (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation